A Test of Competing Hypotheses about Homicide Following Terrorist Attacks: An Interrupted Time Series Analysis of September 11 and Oklahoma City - Pridemore, William Alex (Journal of quantitative criminology, 2008)
There is substantial evidence that catastrophic events, including terrorist attacks, lead to increased levels of post-traumatic stress, especially in communities in close proximity to the incident. Some scholars also argue that these events disrupt social organization. On the other hand, many contend that these incidents produce social cohesion as community members coalesce to help each other in time of need. These ideas have resulted in competing hypotheses in the literature. The first is that violence will increase in the wake of catastrophic events due to heightened levels of individual stress and community disorganization. The second is that violence will decline after these events because of increased social cohesion, especially in the face of an outside threat. In order to test these competing hypotheses, we employed autoregressive integrated moving average (ARIMA) techniques to model the impact of the Oklahoma City bombing and the September 11 attacks on monthly homicide counts at the local, state, and national level. Unlike prior studies that provided evidence of an effect but did not use rigorous time-series techniques, we found no support for either of the competing hypotheses. We conclude that while such catastrophic events may have an effect on individual and collective efficacy well beyond the immediate impact of the incidents, these effects are not strong enough to influence homicide rates.